Communication Strategy of Dompet Dhuafa Yogyakarta in Increasing Ziswaf and Maintaining Muzakki's Trust amid the Covid-19 Pandemic - Pontas, Sutan Kumala; Ridho, Ali; M, Ridzki; Hunawa, Rahmawati (Ahsan: Jurnal Dakwah dan Komunikasi, 2025)
This study analyzes the communication strategy of Dompet Dhuafa Yogyakarta in the midst of the socio-economic crisis during the Covid-19 pandemic by setting four problem formulations, namely (1) How is Dompet Dhuafa Yogyakarta's communication strategy in increasing Ziswaf income in the midst of the Covid-19 Pandemic; (2) How is Dompet Dhuafa's communication effort in maintaining Muzakki in the midst of the Covid-19 Pandemic; (3) Supporting factors for Dompet Dhuafa Yogyakarta's communication in increasing Ziswaf; and (4) Factors inhibiting Dompet Dhuafa Yogyakarta's communication in increasing Ziswaf during Covid 19. The method used in this research is descriptive-qualitative with a case study model. Data collection uses interview, observation, and documentation methods. The results of the study are (1) Dompet Dhuafa Yogyakarta's communication strategy in increasing and maintaining muzakki, namely through digital marketing strategies, utilization of social media and utilization of print media, (2) in maintaining muzakki's trust using Case Relathionship Management (CRM) and selection of communicators in delivering the message, (3) The supporting factors, the number of volunteers, social media, and partners who joined in breaking the spread of Covid-19, and the (4) inhibiting factors are, Covid-19, media, and adaptation.